(untitled) (Journal of the College of Basic Education, 2022)
This research is a documentation of an archaeological site that was unknown to researchers and those interested in the ancient Yemeni civilization. The research consists of two axes, one of which is concerned with monitoring the archaeological evidence found in the Jabal Al-Aswad site, and documenting them, including rock drawings, traces of architectural buildings. The other includes the study and analysis of a group of new inscriptions and scribbles written in the Sabaean language and in Al-Musnad script on stones and rocks, where a brief description of the inscriptions was presented, and its text was written in Arabic calligraphy, then its content was transferred to classical Arabic and its vocabulary was studied in an analytical, linguistic and historical study.